STUDI ANATOMI ENDOFITIK Rafflesia patma DI DALAM INANG Tetrastigma sp. - Mursidawati, Sofi; Sunaryo, Sunaryo (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2012)
As an endoparasite, growth and development of Rafflesia occurred inside the host tissue. ThisÂ cryptic habit is one factor hindering our understanding on how the relationship of host-parasite began. The anatomical study on host-parasite tissue is the approached used in this study. Using infected root tissue of Rafflesia patma, anatomical figures depicting the early event of infection to perfect stage of a flower was derived. However, more study is still required to completely represent the whole life growth and development of Rafflesia during its early stage as endophyte.